(untitled) (Innovative professional education, 2023)
The development of socio-humanitarian education in the legislation of Ukraine is characterized. The problem of marginalization of national pedagogical science in general and the process of education in higher education institutions is outlined. The ways of restoring the status of socio-humanitarian education in the state educational policy of Ukraine are determined.